Dampak Program Beasiswa “Bakti BCA” terhadap Mahasiswa Universitas Tanjungpura Pontianak - Fiani, Veronica Egenia Aulia; AP, Margaretha Andriani; Ng, Amelia (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This research discusses the impact of the Bakti BCA scholarship on Tanjungpura University students. The aim of this research is to find out what impacts students feel when they receive the Bakti BCA scholarship at Tanjungpura University. The analytical tool used in this research is stakeholder theory, in this theory banks not only operate for their own interests but provide benefits to their stakeholders. This research used qualitative research methods and chose Tanjungpura University students as informants for this research. The data analysis technique used is interviews, where this technique is carried out through questions asked verbally to respondents and also carried out face to face. The results of this research show that there are impacts from providing BCA scholarships, including helping with access to education, meeting education costs, guaranteed living costs, increasing learning motivation, increasing achievement, reducing educational inequality, and providing career opportunities.Keywords: Scholarship, students, CSR, impact